2021
DOI: 10.3389/fpsyg.2021.677137
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Exploration of Sports Sponsorship: Activation of Experiential Marketing, Sponsorship Satisfaction, Brand Equity, and Purchase Intention

Abstract: The purpose of this study is to investigate the relationship between the activation of experiential marketing, satisfaction with sponsored sporting events, brand equity, and subsequent product purchase intentions in a small-scale sponsorship campaign. Survey data were collected from 238 actual runners in the terminal rest area after they had completed a race. Structural equation modeling with the bootstrap method was carried out to examine the proposed hypotheses. Results revealed that in terms of product purc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 76 publications
(100 reference statements)
0
10
0
1
Order By: Relevance
“…More specifically, brand equity can positively or negatively affect the value of goods and services, as brand image is strongly related to a consumer's mindset about a brand (Farquhar, 1989). Thus, sport organizations strive for high levels of brand equity which can impact purchase intention (Hsiao et al, 2021;Jalilvand et al, 2011).…”
Section: Brand Equitymentioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, brand equity can positively or negatively affect the value of goods and services, as brand image is strongly related to a consumer's mindset about a brand (Farquhar, 1989). Thus, sport organizations strive for high levels of brand equity which can impact purchase intention (Hsiao et al, 2021;Jalilvand et al, 2011).…”
Section: Brand Equitymentioning
confidence: 99%
“…Regarding partnerships, Hsiao et al (2021) found that brand equity impacts the purchase intention of a sponsored entity. Previous scholars have used brand equity as a mediator between marketing mix elements and consumers' intentions (Yoo et al, 2000).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…La experiencia se considera uno de los aspectos esenciales que los gerentes deben considerar en su estrategia de marketing mix (Brakus et al, 2009;Castañeda et al, 2017). En la tabla 01 se observa que la correlación de las variables del coeficiente de Pearson, toma un valor de 0,578; el resultado Barboza Seclén, Diana Makarena; Miranda Guerra, María del Pilar; Cespedes Ortiz, Cristhian Paul; Esparza Huamanchumo, Rosse Marie Marketing experiencial y el valor de marca en el sector gastronómico_______________ 2021) reconocen en las empresas relacionadas al sector gastronómico, la importancia de generar experiencias de marketing, dado que los comensales buscan cada vez servicios de comidas con características únicas también mencionaron que la experiencia de marca destaca como un componente para construir un valor de marca sólido (Hsiao et al, 2021).…”
Section: Tabla 1 Relación De La Variable Marketing Experiencial Y Var...unclassified
“…Media also help sponsors expand their businesses and grow their own audiences and fan bases (Kelly & Van der Leij, 2021). Recently, a number of studies discovered the use of sponsorship activation in sponsorship transferred favourable attitudes, experiences, intention, positive word of mouth, and brand equity among consumers (Burton & Schlieman, 2021;Goebert & Greenhalgh, 2020;Hsiao, Tang, & Su, 2021). Taking these factors into account, the current study intends to explore the role of media as a communication tool in sponsorship programmes, particularly in the business-tobusiness (B2B) setting.…”
Section: Introductionmentioning
confidence: 99%